2014
DOI: 10.1021/nn503431x
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Nanoparticle-Based Peptide Therapeutics and Combined Hyperthermia for Enhanced Cancer Cell Apoptosis

Abstract: Mitochondria-targeting peptides have garnered immense interest as potential chemotherapeutics in recent years. However, there is a clear need to develop strategies to overcome the critical limitations of peptides, such as poor solubility and the lack of target specificity, which impede their clinical applications. To this end, we report magnetic core–shell nanoparticle (MCNP)-mediated delivery of a mitochondria-targeting pro-apoptotic amphipathic tail-anchoring peptide (ATAP) to malignant brain and metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 50 publications
(118 reference statements)
2
76
0
1
Order By: Relevance
“…Effective drug delivery by nanocarriers has been intensively investigated using dendrimers [1,2], polymeric micelles [3], liposomes [4,5], carbon-based materials [6e8], magnetic particles [9,10], and noble metal nanoparticles (NPs) [7,11]. Nanocarriers were developed to protect drugs from premature degradation and to enhance drug absorption into specific tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Effective drug delivery by nanocarriers has been intensively investigated using dendrimers [1,2], polymeric micelles [3], liposomes [4,5], carbon-based materials [6e8], magnetic particles [9,10], and noble metal nanoparticles (NPs) [7,11]. Nanocarriers were developed to protect drugs from premature degradation and to enhance drug absorption into specific tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Most of multifunctional nanotheranostic systems are actively targeted against the integrins (Liu P et al, 2012;Shah et al, 2014) and MMPs (Hollis et al, 2014) imaging of the TMT-LS-DiD treated animals revealed that these nanoparticles accumulated only in the metastatic foci and not in the normal tissues . A multifunctional nanocarrier system for brain metastatic disease was formulated based on poly (methacrylic acid)-polysorbate 80-grafted starch nanoparticles loaded with gadolinium and doxorubicin and tested.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…23,24 Earlier studies conducted with Fe-bLf NCs nanotherapeutics showed a multifunctional nature in terms of modulation of critical anticancersignaling nodes, boosting the immunosignaling mechanism by enriching the production of B cells, natural killer cells, and interleukin expression. Furthermore, Fe-bLf and Fe-bLf nanoformulations showed increased cytokine expression, promoting macrophage and phagocytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Future considerations for work in this area relate to uncover the in vivo anticancer-signaling and stem cell-signaling mechanisms of Zn-Fe-bLf NCs in colon and breast tumors and improvisation of Zn-Fe-bLf NCs for enhancing selective therapeutic effects in combination with imaging strategies, such as ultrasound MRI, single photon-emission CT-and magnetic ultrasound-based imaging modalities. 23,[39][40][41][42] Further, new technologies, such as aptamers, locked nucleic acid conjugates, and nanobodies are to be employed in a combinative treatment regime for the safe management of cancer therapies. 4,43,44 For personal use only.…”
Section: Discussionmentioning
confidence: 99%